2004
DOI: 10.1002/cm.20003
|View full text |Cite
|
Sign up to set email alerts
|

Roles for two partially redundant α‐tubulins during mitosis in early Caenorhabditis elegans embryos

Abstract: The Caenorhabditis elegans genome encodes multiple isotypes of alpha-tubulin and beta-tubulin. Roles for a number of these tubulins in neuronal development have been described, but less is known about the isoforms that function during early embryonic development. Microtubules are required for multiple events after fertilization produces a one-cell zygote in C. elegans, including pronuclear migration, mitotic spindle assembly and function, and proper spindle positioning. Here we describe a conditional and domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…There are nine -tubulin and six -tubulin isoforms predicted in the C. elegans genome (C. elegans Sequencing Consortium, 1998). Previous studies suggested functional redundancy of some -and -tubulin isotypes (Driscoll et al, 1989;Lu et al, 2004;Phillips et al, 2004;Wright and Hunter, 2003). Nocodazole, which disrupts microtubule polymerization regardless of subunit composition, provides a convenient tool with which to analyze the function of microtubules in biological processes.…”
Section: Microtubules Are Required For Left-right Awc Neuronal Asymmetrymentioning
confidence: 99%
“…There are nine -tubulin and six -tubulin isoforms predicted in the C. elegans genome (C. elegans Sequencing Consortium, 1998). Previous studies suggested functional redundancy of some -and -tubulin isotypes (Driscoll et al, 1989;Lu et al, 2004;Phillips et al, 2004;Wright and Hunter, 2003). Nocodazole, which disrupts microtubule polymerization regardless of subunit composition, provides a convenient tool with which to analyze the function of microtubules in biological processes.…”
Section: Microtubules Are Required For Left-right Awc Neuronal Asymmetrymentioning
confidence: 99%
“…According to this model, multiple genes allow the maintenance of a stable pool of available monomers and dimers. The small amount of sequence variation within the a-and b-tubulin families supports this idea, as do studies of functionally redundant mitotic tubulins in C. elegans Lu et al 2004;Phillips et al 2004;Lu and Mains 2005). The alternative hypothesis proposes that specific structures, e.g., ciliary axonemes or axonal microtubules, rely on tubulins optimized for specific roles.…”
mentioning
confidence: 93%
“…Some of these genes, particularly tba-1, tba-2, tbb-1, and tbb-2, are expressed broadly during embryogenesis and function redundantly in spindle assembly and positioning Lu et al 2004;Phillips et al 2004;Lu and Mains 2005). tba-1 and tbb-2 have also been recently shown to be important for axon outgrowth and synaptogenesis (Baran et al 2010).…”
mentioning
confidence: 99%
“…E.g. tac-1 is essential for pronuclear migration [10]; loss of function of the gamma-tubulin gene by RNAi does not affect pronuclear migration [11]; pronuclei treated with antibodies will not move at all [12][13]; some special biochemical treatments may [14] or may not [15][16][17] affect to the motion; mutant defected pronuclei migrate abnormally [18][19][20][21] or normally [22]. We think all of the above results are caused by normal or abnormal EMF (EF) distribution.…”
Section: Discussionmentioning
confidence: 99%